CFD-based study of flow field characteristics and clogging in horizontal flow constructed wetlands - Liu, Wen; Li, Shitao; Yang, Kai; Zeng, Xianqiu; Li, Yiyong; Zou, Mengyao; Deng, Yili; Qian, Wei (Frontiers in Environmental Science, 2025)
The flow field distribution and clogging process in HFCWs are complex, the hydraulic characteristics, distribution and size of dead zone of HFCW were studied by using the Computational Fluid Dynamics (CFD). The results showed that (1) The ceramsite system’s filtration efficacy in treating wastewater is primarily driven by deep filtration processes. The distribution of water flow within the ceramsite wetland system is more homogenous than that observed in the blast furnace slag wetland system. Furthermore, the ceramsite system exhibits enhanced utilization of the primary bed area, the underlying drainage layer, and the catchment zone. (2) The blast furnace slag system possesses a smaller porosity and particle size distribution, which results in non-uniform flow rates and pressure distributions. Consequently, this system is prone to clogging, leading to a decline in both hydraulic performance and the overall functionality of the wetland. (3) The ceramsite system exhibits a lower occurrence of dead zones within the main bed compared to the blast furnace slag system, with a reduction of 12.58% and 27.93% in the dead zone percentages, respectively. This suggests that the ceramsite system outperforms the blast furnace slag system in terms of hydraulic efficiency, resistance to clogging, and contaminant removal efficacy.